Environmental enrichment and response cost: Immediate and subsequent effects on stereotypy. Issue 1 (14th January 2014) - Watkins, Nicholas; Rapp, John T.
<x xml:space="preserve">Abstract</x> We assessed the immediate and subsequent effects of environmental enrichment (EE) as a stand‐alone intervention and when EE was combined with response cost (RC) for 5 participants using a 2‐component multiple‐schedule design. Environmental enrichment failed to decrease any participant's immediate engagement in stereotypy; however, the addition of RC decreased the immediate engagement in stereotypy for all participants. After the withdrawal of EE plus RC, stereotypy did not immediately increase for 3 of 5 participants.